18 Manipulation Under Anaesthetic for Frozen Shoulder: Does Post-Operative Supervised Physiotherapy Affect the Outcome?. (4th May 2021) - Castelhano, R; Woods, J; Akehurst, H; Mitra, A; James, M; Tasker, A; Woods, D
Abstract: Introduction: This study compares two pathways for patients undergoing MUA for FS, one where physiotherapy advice is only given to the patient (Group 1), and the other where supervised hydrotherapy and physiotherapy occur post operatively (Group 2). Method: A descriptive analysis of pre- and post-operative Oxford Shoulder Scores and change scores were performed. Analysis of covariance (ANCOVA) was used to measure the effect of physiotherapy on post-operative OSS, with pre-operative OSS as the only covariate. Results: The results for post-operative OSS were significantly greater for Group 2 than for Group 1 (40.7 for NHS and 44.7 for private, improvement of 17.32 for NHS and 18.23 for Private). The estimated effect of physiotherapy on postoperative OSS was an increase of 3.2 (95% confidence interval 1.5 – 4.8). Conclusions: We detected a statistically significant increase in post-operative OSS in patients treated for frozen shoulder with MUA + physiotherapy compared with patients receiving MUA plus advice alone. These results suggest that physiotherapy does confer a real benefit, however the increased OSS is below the clinically significant level. Therefore, in a resource poor environment, such as may exist after COVID in many health care systems, MUA plus physio advice alone gives an excellent outcome for the treatment of FS.